Modeling Vorticity-Driven Wildfire Behavior Using Near-Field Techniques - Sharples, Jason J.; Hilton, James E. (Frontiers in Mechanical Engineering, 2020)
Dynamic modes of fire propagation present a significant challenge for operational fire spread simulation. Current two-dimensional operational fire simulation platforms are not generally able to account for the complex interactions that drive such behaviours, and while fully coupled fire atmosphere models are able to account for dynamic effects to an extent, their computational demands are prohibitive in an operational context. In this paper we consider techniques for extending two-dimensional fire spread simulators so that they are able to simulate certain dynamic fire behaviours. In particular, we consider modelling vorticity-driven lateral spread (VLS), which is characterised by rapid lateral fire propagation across steep, leeward slopes. Specifically, we consider modelling the influence of the fire on the local surface airflow via a ‘pyrogenic potential’ model, which allows for vertical vorticity effects (in a near-field sense) using the Helmholtz decomposition. The ability of the resulting model to emulate fire propagation associated with VLS is demonstrated using a number of examples.